Promoting HIV/AIDS Prevention through Soap Operas - William Brown; Steven Kiruswa, Steven Kiruswa,; Benson P. Fraser Benson P. Fraser (Communicare)
In the past three decades television soap operas have been used as a means of health education and persuasion. In recent years, the proliferation of entertainment television worldwide has made the soap opera a powerful source of educational and social messages. One of the most critical global health issues of today is the need to reduce HIV/AIDS infection, particularly on the continent of Africa. In the 1990s, the country of Tanzania broadcast a highly effective radio soap opera to promote HIV/AIDS prevention. In 2000, Tanzania again employed the use of the soap opera to address HIV/AIDS as well as other social issues, this time through television. Our research indicates that the Tanzanian television soap opera employed in this effort, Maisha, effectively promoted HIV/AIDS prevention among television viewers. In particular, those who were more involved with Mashaka, the star of Maisha, were more powerfully influenced by the health messages communicated through the programme. The implications of this research for using entertainment for HIV/AIDS prevention are discussed